Technological innovation and social construction of Makassar film industry’s production and distribution - Puspitasari, Lilis; Bajari, Atwar; Hidayat, Dadang Rahmat; Cho, Sung Kyum (Jurnal Kajian Komunikasi, 2024)
Background: Cinematography has evolved significantly with technological advancements. In Makassar, Indonesia, film distribution faced challenges due to limited cinemas and competition with imported films. The research explores how technology has transformed film production, distribution, and promotion in Makassar. It addresses gaps in understanding regional cinema’s adaptation to technological changes. Purpose: This research aimed to examine the role of technology in transforming film production and distribution around Makassar. Methods: The study employed qualitative research methods with a case study approach. Data was collected through interviews and observation with key figures in Makassar’s film industry, including producers, directors, and editors. The research applied the Social Construction of Technology (SCoT) theory to analyze how social factors shaped and influenced technology. Results: In pre-production, technology helps with audience research and visual concept design; In the production stage, digital cameras increase image quality and flexibility. In post-production, advanced software allows for better editing and visual effects despite limited local experts; In distribution, it expanded from theaters to streaming platforms, reaching a wider audience. All stages benefit from better collaboration through digital tools. Conclusion: This study found that technology has significantly impacted all stages of filmmaking in Makassar. At the pre-production stage, digital tools facilitate collaboration and audience research. During production, advanced cameras and equipment enhance visual quality and creative possibilities. Post-production benefits from sophisticated editing software, although some processes still require expertise outside the region. Film distribution does not rely on movie theatres; it is distributed through platforms like Netflix, Disney+, Hulu, and Prime Video. Implications: Specifically, findings suggest that regional filmmakers should invest in digital skills and explore diverse distribution channels. Theoretically, the study contributes to understanding how SCoT applies in regional film contexts. It highlights the importance of considering local social dynamics in technological adoption within creative industries.